NiOx isopropanol dispersion liquid as well as preparation method and application thereof
By preparing NiOx isopropanol dispersion, the problem of limited application of NiOx nanomaterials in perovskite solar cells is solved, the construction of a uniform hole transport layer is achieved, the efficiency and stability of solar cells are improved, and the convenience of long-term and stable storage is provided.
Patent Information
- Application Number
- CN202411839025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the application of NiOx nanomaterials in perovskite solar cells is limited, especially due to performance and life problems caused by moisture residues.
The oxalic acid, particle size control agent, co-solvent, defect inhibitor and organic solvent are mixed with the first reaction system to form a first reaction system, and the nickel salt is dissolved in the organic solvent to form a second reaction system. By controlling the pH and reaction time, a nickel oxalate sol dispersion system is obtained. Then calcined and ball milled to obtain NiOx nano powder, and finally mixed with isopropanol and sonicated to prepare a NiOx isopropanol dispersion.
A uniform hole transport layer is achieved on the perovskite film, avoiding interference from moisture and other organic solvents, significantly improving the photoelectric conversion efficiency and long-term stability of solar cells, and the dispersion can be stored stably for more than one year under room temperature conditions.
Smart Images

Figure CN119683698A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells and particularly relates to a NiO x Isopropyl alcohol dispersion, preparation method and application thereof. Background Art
[0002] In an inverted perovskite solar cell, the hole transport layer is placed on the transparent electrode, followed by the light absorbing layer. The main advantage of this structure is that light first passes through the hole transport layer, which can make the cell have a smaller hysteresis and a higher filling rate, and the deposition of the electron transport layer does not affect the perovskite layer.
[0003] NiO x As a commonly used hole transport layer material in inverse perovskite solar cells, NiO has the advantages of being cheap, stable, and easy to prepare. x Nanomaterials are dispersed in aqueous solutions, which limits their use in formal devices; even in trans devices, if NiO x Improper annealing of the NiO layer will result in residual moisture, which will also damage the perovskite and affect the performance and life of the device. x The organic dispersion of nickel oxide is particularly important. Experiments have found that methanol and ethanol will dissociate perovskite due to their high polarity, while isopropanol has a low polarity and is less destructive to perovskite. Therefore, it is particularly important to study the isopropanol dispersion of nickel oxide. Summary of the invention
[0004] The purpose of the present invention is to provide a NiO x Isopropyl alcohol dispersion and its preparation method and application are used to solve the problem of NiO in the prior art x Application limitations of nanomaterials in perovskite solar cells.
[0005] The technical solution of the present invention is as follows:
[0006] A NiO x The preparation method of isopropanol dispersion comprises the following steps:
[0007] S1. The oxalic acid, particle size control agent, cosolvent, defect inhibitor and organic solvent are mixed to form a first reaction system, the cosolvent and defect inhibitor are high boiling point oxygen-containing, nitrogen-containing polymers;
[0008] S2. dissolving the nickel salt in the above organic solvent at 10-30°C to obtain a nickel precursor solution to form a second reaction system;
[0009] S3. The first reaction system was uniformly added dropwise to the second reaction system, the pH was controlled at 1-4, and the reaction was performed for 0.2-4h to obtain a nickel oxalate sol dispersion system;
[0010] S4. Centrifuging the nickel oxalate sol dispersion system, washing the nickel oxalate sol several times with the organic solvent until there is no nickel salt or free oxalic acid;
[0011] S5. The pure nickel oxalate sol obtained in S4 was calcined at 230℃-500℃ for 1-24h to obtain black NiO x calcined body;
[0012] S6. NiO x The calcined body is ball milled in a ball mill for 0.5-24h to obtain NiO x Nano powder;
[0013] S7. NiO x The nanopowder was mixed with isopropanol and ultrasonicated for 0.1-10h under an ultrasonic processor to obtain NiO x Isopropyl alcohol dispersion, NiO x The concentration reaches 0-10wt%.
[0014] Further, the particle size control agent described in S1 is a C2-C5 straight-chain alcohol amine;
[0015] Further, the ratio of oxalic acid, particle size control agent, cosolvent, and defect inhibitor described in S1 is 1:(0.1-10):(0.1-1):(0.05-0.5) in molar ratio;
[0016] Furthermore, the molar ratio of the nickel salt concentration in S2 is 0.01-0.3 mol / L.
[0017] Furthermore, the pH in S3 is controlled by the amount of nickel salt, oxalic acid, and particle size control agent. Calculated by mass ratio, nickel salt: oxalic acid: particle size control agent = 1: (0.5-3): (0.5-30).
[0018] NiO prepared by any of the above preparation methods x Isopropyl alcohol dispersion, NiO x The invention comprises nickel(II) oxide and nickel(III) oxide, wherein the molar ratio of nickel(III) to nickel(II) is between 0.1 and 3.
[0019] Furthermore, the nanoparticle structure dispersed therein includes the innermost layer of NiO x Inorganic matter, NiO x The cross-linked polymer on the surface of the inorganic substance and the outermost organic ligand, the cross-linked polymer is a high-boiling point oxygen-containing and nitrogen-containing polymer, and the organic ligand includes oxalate, a particle size control agent, a co-solvent, and a defect inhibitor.
[0020] Furthermore, the content of the organic ligand accounts for 1%-10% of the total weight of the nano material.
[0021] Furthermore, NiO x The size of the nanoparticles is 3-10 nm, and their band gap ranges from 3.6 eV to 4.0 eV.
[0022] As mentioned above, NiO x Application of isopropanol dispersion as hole transport layer in perovskite solar cells.
[0023] The beneficial effects of the present invention are as follows:
[0024] NiO prepared by the present invention x Isopropyl alcohol dispersion can successfully construct a uniform hole transport layer on the perovskite film. This process completely avoids the interference of water, ethanol, and methanol, thereby greatly improving the photoelectric conversion efficiency and long-term stability of perovskite solar cells. In addition, the dispersion can be stably stored for more than one year at room temperature, which greatly facilitates its wide application in industrial production.
[0025] The NiO calcined with nickel oxalate in the present invention x A layer of chemical residues such as oxalic acid will be attached to its surface, so that it can be dispersed in isopropanol, and a particle size control agent is used to control the size of nickel oxalate particles, so that the particle size distribution of the calcined powder will be narrower; high-boiling point oxygen-containing and nitrogen-containing polymers are used to coordinate the surface of nickel atoms in nickel oxalate. During the calcination process, the cross-linking degree of these polymers will increase, forming a network structure with a higher degree of cross-linking, which adheres to the surface of nickel oxide nanoparticles, making it more stable in the dispersion concentration of isopropanol. The reason for adding defect inhibitors is that nickel oxalate is calcined into NiO x After that, more oxygen vacancies and nickel vacancies will be formed, which will form defect states, thereby quenching the carriers and affecting the photoelectric conversion efficiency of the device. The O and N present in the oxygen-containing and nitrogen-containing polymers will coordinate with the oxygen vacancies and nickel vacancies on the surface of nickel oxide to repair the defect states, thereby improving the photoelectric properties of NiOx and its dispersibility in isopropanol.
[0026] The present invention expands NiO x The application potential of isopropyl alcohol dispersion in high-precision and high-efficiency manufacturing processes such as inkjet printing, ultrasonic spraying and slit coating has injected new vitality into the development of new energy materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 NiO prepared by the present invention x Structural diagram.
[0028] Figure 2 NiO prepared by the present invention x TEM image of nanoparticles.
[0029] Figure 3 NiO prepared by the present invention x XRD pattern of nanoparticles.
[0030] Figure 4 NiO prepared by the present invention x UV-visible absorption graph of nanoparticles.
[0031] Figure 5 NiO prepared by the present invention x Thermogravimetric analysis of nanoparticles. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be further described below through embodiments.
[0033] A method for preparing a nickel oxide isopropanol dispersion comprises the following steps:
[0034] S1. mixing oxalic acid, a particle size control agent, a cosolvent, a defect inhibitor and an organic solvent to form a first reaction system;
[0035] S2. Under a temperature of 10-30° C., dissolving the nickel salt in the organic solvent to obtain a nickel precursor solution of a specified concentration to form a second reaction system;
[0036] S3. The first reaction system was uniformly added dropwise to the second reaction system, the pH was controlled at 1-4, and the reaction was performed for 0.2-4h to obtain a nickel oxalate sol dispersion system;
[0037] S4. Centrifuging the nickel oxalate sol dispersion system, washing the nickel oxalate sol several times with the organic solvent until there is no nickel salt or free oxalic acid;
[0038] S5. The pure nickel oxalate sol obtained in S4 was calcined at 230℃-500℃ for 1-24h to obtain black NiO x calcined body;
[0039] S6. NiO x The calcined body is ball milled in a ball mill for 0.5-24h to obtain NiO x Nano powder;
[0040] S7. NiO x The nanopowder was mixed with isopropanol and ultrasonicated for 0.1-10h under an ultrasonic processor to obtain NiO x Isopropyl alcohol dispersion.
[0041] The particle size control agent described in S1 is a C2-C5 straight-chain alcohol amine, for example, one of ethanol, propanolamine, butanolamine, and pentanolamine, preferably ethanolamine.
[0042] The co-solvents and defect inhibitors described in S1 are high-boiling oxygen-containing and nitrogen-containing polymers, for example: polyethylene glycols, such as PEG200, PEG400, PEG600, PEG800, PEG1000; polyvinyl pyrrolidone, such as PVP(K12), PVP(K15), PVP(K17), PVP(K25), PVP(K30), PVP(K60), PVP(K90); polyethylene imine, such as having a molecular weight of 1000-100000.
[0043] The organic solvent described in S1 can be selected from but is not limited to one of methanol, ethanol, isopropanol, and ethylene glycol monomethyl ether.
[0044] The nickel salt in S2 can be selected from but not limited to nickel nitrate and its hydrate, nickel chloride and its hydrate, nickel acetate and its hydrate, nickel sulfate and its hydrate, nickel bromide and its hydrate, nickel acetylacetonate and its hydrate, nickel dibutyldithiocarbamate, nickel diethyldithiocarbamate, nickel oxalate, nickel phosphate, nickel xanthate, nickel ethylenediaminetetraacetic acid, nickel isopropoxide, nickel 8-hydroxyquinoline, nickel stearate, nickel oleate, nickel hypophosphite and its hydrate, nickel fluoride, basic nickel carbonate, nickel perchlorate, nickel benzoate, nickel thiocyanate, and nickel trifluoromethanesulfonate.
[0045] The uniform speed in S3 is achieved by means of a metering pump and a peristaltic pump, and the pump speed is controlled to complete the dripping of the first reaction system in 1-2 hours.
[0046] The power of the ultrasonic processor in S7 is 100-800W, the frequency is 20-40KHz, and the ultrasonic time can also be selected to be 0.1-10h.
[0047] The present invention also provides a NiO x The isopropanol dispersion is prepared according to the above method. The nickel oxide isopropanol dispersion comprises NiO x Inorganic, NiO x The organic ligand on the surface is composed of isopropanol. x The concentration of the dispersion can reach 10 wt%. The band gap is calculated to be in the range of 3.6 eV to 4.0 eV. The calculation method is well known to those skilled in the art, for example, it can be calculated by the Tauc Plot method, which will not be described in detail here.
[0048] According to another aspect of the present invention, a formal perovskite solar cell is provided, comprising an anode, an electron transport layer, a light absorbing layer, a hole transport layer, and a cathode, wherein the hole transport layer is prepared from the above-mentioned nickel oxide nano isopropanol dispersion by spin coating, printing, spraying, or scraping.
[0049] Nickel oxalate (NiC2O4) as calcined NiO xThe calcination equation of the precursor is as follows:
[0050]
[0051] Conventional nickel oxalate cannot be dispersed in isopropanol after calcination because the surface of NiOx is composed of dangling bonds of Ni and O, which have no dispersibility to isopropanol. The NiOx in the present application is pre-treated, and the dangling bonds on the surface of the calcined NiOx are bonded by organic matter, which has a strong hydrogen bonding effect on isopropanol, thereby improving the dispersibility and repairing the defective energy levels of NiOx, thereby ultimately improving the performance of perovskite solar cells.
[0052] Embodiment 1
[0053] S1. 0.12 mol oxalic acid, 0.06 mol ethanolamine, 0.05 mol PEG400, 0.005 mol PVP (K30), and 300 ml ethanol were mixed to form a first reaction system;
[0054] S2. At room temperature, 0.1 mol Ni(NO3)2 was dissolved in 300 ml of ethanol to obtain a nickel precursor solution to form a second reaction system;
[0055] S3. The first reaction system was uniformly added dropwise to the second reaction system, the pH was controlled at 2, and the nickel oxalate sol dispersion system was obtained after the reaction for 2 h;
[0056] S4. Centrifuge the nickel oxalate sol dispersion system, and wash the nickel oxalate sol with ethanol three times;
[0057] S5. The pure nickel oxalate sol obtained in S4 was calcined at 320°C for 2h to obtain a black NiOx calcined body;
[0058] S6. NiO x The calcined body was ball milled in a ball mill for 12 h to obtain NiO x Nano powder;
[0059] S7. NiO x The nanopowder was mixed with isopropanol and ultrasonicated for 2 h under a 600W, 20KHZ ultrasonic processor to obtain 3wt% NiO x Isopropyl alcohol dispersion;
[0060] Embodiment 2
[0061] S1. 0.2 mol oxalic acid, 0.04 mol 4-amino-1-butanol, 0.05 mol PEG200, 0.005 mol PVP (K18), and 300 ml methanol were mixed to form a first reaction system;
[0062] S2. At room temperature, 0.1 mol Ni(Ac)2.4H2O was dissolved in 300 ml of methanol to obtain a nickel precursor solution to form a second reaction system;
[0063] S3. The first reaction system was uniformly added dropwise to the second reaction system, the pH was controlled at 1.8, and the nickel oxalate sol dispersion system was obtained after the reaction for 2 h;
[0064] S4. Centrifuge the nickel oxalate sol dispersion system, and wash the nickel oxalate sol with methanol three times;
[0065] S5. The pure nickel oxalate sol obtained in S4 was calcined at 350°C for 2h to obtain black NiO x calcined body;
[0066] S6. NiO x The calcined body was ball milled in a ball mill for 12 h to obtain NiO x Nano powder;
[0067] S7. NiO x The nanopowder was mixed with isopropanol and ultrasonicated for 1 h under a 400W, 20KHZ ultrasonic processor to obtain a 5wt% NiOx isopropanol dispersion;
[0068] Embodiment 3
[0069] S1. 0.22 mol oxalic acid, 0.03 mol ethanolamine, 0.02 mol PEG800, 0.001 mol PVP (K90), and 600 ml ethanol were mixed to form a first reaction system;
[0070] S2. At room temperature, 0.1 mol NiCl2·6H2O was dissolved in 600 ml ethanol to obtain a nickel precursor solution to form a second reaction system;
[0071] S3. The first reaction system was uniformly added dropwise to the second reaction system, the pH was controlled at 2.3, and the nickel oxalate sol dispersion system was obtained after the reaction for 1 h;
[0072] S4. Centrifuge the nickel oxalate sol dispersion system, and wash the nickel oxalate sol with ethanol three times;
[0073] S5. The pure nickel oxalate sol obtained in S4 was calcined at 400℃ for 2h to obtain gray-black NiO x calcined body;
[0074] S6. NiO x The calcined body was ball milled in a ball mill for 4 h to obtain NiO x Nano powder;
[0075] S7. NiO xThe nanopowder was mixed with isopropanol and ultrasonicated for 2 h under a 600 W, 20 KHZ ultrasonic processor to obtain an 8 wt % NiOx isopropanol dispersion;
[0076] Embodiment 4
[0077] This embodiment provides an inverted solar perovskite cell device, and its manufacturing method comprises the following steps: spin coating the NiO in Example 1 on the ITO anode layer; x The nanomaterial is dispersed in isopropanol and then annealed at 120°C for 30 minutes to form a hole transport layer; an absorption layer is formed by spin coating a perovskite solution on the hole transport layer as a carrier; an isopropanol solution of zinc oxide is spin coated on the absorption layer and dried to form an electron transport layer; finally, an Au cathode electrode layer is evaporated and packaged to form a perovskite solar cell device.
[0078] The NiO in the above embodiment x Isopropanol dispersion, the device was manufactured according to the device preparation process of Example 5, and the device performance parameters are shown in Table 1:
[0079] Comparative Example 1
[0080] S1. At 25°C, 0.3 mol of nickel nitrate and 1 L of water were mixed to obtain a first reaction system;
[0081] S2. 0.6 mol of NaOH was added to the first reaction system, and the reaction was continued for 2 h to obtain a Ni(OH)2 sol dispersion system;
[0082] S3. The Ni(OH)2 sol dispersion is centrifuged and washed twice with water until the nitrate ions are completely eluted;
[0083] S4. S4 was calcined at 280℃ for 1h to obtain black NiO x calcined body;
[0084] S5. NiO x The nanopowder was ultrasonicated for 1 h under an ultrasonic probe to obtain NiO x Nanoparticles in water.
[0085] Table 1: Comparison of device performance in various embodiments
[0086] serial number Bandgap(eV) PCE(%) FF(%) Stabilization time Embodiment 1 3.69 21.5 74.5 75 days Embodiment 2 3.75 21.9 75.2 35 days Embodiment 3 3.72 22.1 76.5 40 days Embodiment 4 3.74 21.3 74.0 65 days Comparative Example 1 3.68 10.2 50.6 5 minutes
[0087] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A NiO x The method for preparing an isopropanol dispersion is characterized in that: The following steps are involved: S1. The oxalic acid, particle size control agent, cosolvent, defect inhibitor and organic solvent are mixed to form a first reaction system, the cosolvent and defect inhibitor are high boiling point oxygen-containing, nitrogen-containing polymers; S2. dissolving the nickel salt in the above organic solvent at 10-30°C to obtain a nickel precursor solution to form a second reaction system; S3. The first reaction system was uniformly added dropwise to the second reaction system, the pH was controlled at 1-4, and the reaction was performed for 0.2-4h to obtain a nickel oxalate sol dispersion system; S4. Centrifuging the nickel oxalate sol dispersion system, washing the nickel oxalate sol several times with the organic solvent until there is no nickel salt or free oxalic acid; S5. The pure nickel oxalate sol obtained in S4 was calcined at 230℃-500℃ for 1-24h to obtain black NiO x calcined body; S6. NiO x The calcined body is ball milled in a ball mill for 0.5-24h to obtain NiO x Nano powder; S7. NiO x The nanopowder was mixed with isopropanol and ultrasonicated for 0.1-10h under an ultrasonic processor to obtain NiO x Isopropyl alcohol dispersion, NiO x The concentration reaches 0-10wt%.
2. NiO according to claim 1 x The preparation method of isopropanol dispersion is characterized by: The particle size control agent described in S1 is a C2-C5 straight-chain alcohol amine.
3. NiO according to claim 1 x The preparation method of isopropanol dispersion is characterized by: The molar ratio of the oxalic acid, particle size control agent, cosolvent and defect inhibitor described in S1 is 1:(0.1-10):(0.1-1):(0.05-0.5).
4. NiO according to claim 1 x The preparation method of isopropanol dispersion is characterized by: The molar ratio of nickel salt concentration in S2 is 0.01-0.3 mol / L.
5. NiO according to claim 1 x The preparation method of isopropanol dispersion is characterized by: The pH in S3 is controlled by the amount of nickel salt, oxalic acid, and particle size control agent. Calculated by mass ratio, nickel salt: oxalic acid: particle size control agent = 1: (0.5-3): (0.5-30).
6. NiO prepared by any one of the preparation methods of claims 1 to 5 x Isopropyl alcohol dispersion, NiO x The invention comprises nickel(II) oxide and nickel(III) oxide, wherein the molar ratio of nickel(III) to nickel(II) is between 0.1 and 3.
7. NiO according to claim 6 x Isopropanol dispersion, characterized in that: The nanoparticle structure dispersed in it includes the innermost layer of NiO x Inorganic substances, NiO x The cross-linked polymer on the surface of the inorganic substance and the outermost organic ligand, the cross-linked polymer is a high-boiling point oxygen-containing and nitrogen-containing polymer, and the organic ligand includes oxalate, a particle size control agent, a co-solvent, and a defect inhibitor.
8. NiO according to claim 7 x Isopropanol dispersion, characterized in that: The content of the organic ligand accounts for 1%-10% of the total weight of the entire nano material.
9. NiO according to claim 8 x Isopropanol dispersion, characterized in that: Among them, NiO x The size of the nanoparticles is 3-10 nm, and their band gap ranges from 3.6 eV to 4.0 eV.
10. NiO according to claim 6 x Application of isopropanol dispersion as hole transport layer in perovskite solar cells.